Bifunctional phase-transfer catalysis in the asymmetric synthesis of biologically active isoindolinones - Di Mola, Antonia; Tiffner, Maximilian; Scorzelli, Francesco; Palombi, Laura; Filosa, Rosanna; De Caprariis, Paolo; Waser, Mario; Massa, Antonio (Beilstein Journal of Organic Chemistry, 2015)
New bifunctional chiral ammonium salts were investigated in an asymmetric cascade synthesis of a key building block for a variety of biologically relevant isoindolinones. With this chiral compound in hand, the development of further transformations allowed for the synthesis of diverse derivatives of high pharmaceutical value, such as the Belliotti (S)-PD172938 and arylated analogues with hypnotic sedative activity, obtained in good overall total yield (50%) and high enantiomeric purity (95% ee). The synthetic routes developed herein are particularly convenient in comparison with the current methods available in literature and are particularly promising for large scale applications.
Keywords: asymmetric synthesis; Belliotti (S)-PD 172938; heterocycles; isoindolinones cascade reactions; phase transfer catalysts

(untitled) - Speck, K.; Magauer, T. (Beilstein J. Org. Chem., 2013)

(untitled) - Di Mola, A.; Palombi, L.; Massa, A. (Curr. Org. Chem., 2012)

Targets in Heterocyclic Systems: Chemistry and Properties - Di Mola, A.; Palombi, L.; Massa, A. (An overview on asymmetric synthesis of 3-substituted indolinones, 2014)
See for a review on asymmetric synthesis of isoindolinones.

(untitled) - Kanamitsu, N.; Osaki, T.; Itsuji, Y.; Yoshimura, M.; Tsujimoto, H.; Soga, M. (Chem. Pharm. Bull., 2007)

PCT Patent - Toyooka, K.; Kanamitsu, N.; Yoshimura, M.; Kuriyama, K. S.; Tamura, H.; Takashi, K. S. (Isoindoline derivatives, 2003)

(untitled) - Hussein, Z.; Mulford, D. J.; Bopp, B. A.; Granneman, G. R. (Br. J. Clin. Pharmacol., 1993)

(untitled) - Kondo, T.; Yoshida, K.; Yamamoto, M.; Tanayama, S. (Arzneim. Forsch., 1996)

(untitled) - Belliotti, T. R.; Brink, W. A.; Kesten, S. R.; Rubin, J. R.; Wustrow, D. J.; Zoski, K. T.; Whetzel, S. Z.; Corbin, A. E.; Pugsley, T. A.; Heffner, T. G.; Wise, L. D. (Bioorg. Med. Chem. Lett., 1998)

(untitled) - Lebrun, S.; Sallio, R.; Dubois, M.; Agbossou-Niedercorn, F.; Deniau, E.; Michon, C. (Eur. J. Org. Chem., 2015)

(untitled) - Bisai, V.; Unhale, R. A.; Suneja, A.; Dhanasekaran, S.; Singh, V. K. (Org. Lett., 2015)

(untitled) - Li, T.; Zhou, S.; Wang, J.; Aceña, J. L.; Soloshonok, V. A.; Liu, H. (Chem. Commun., 2015)

(untitled) - Scorzelli, F.; Di Mola, A.; Palombi, L.; Massa, A. (Molecules, 2015)

(untitled) - Nishimura, T.; Noishiki, A.; Ebe, Y.; Hayashi, T. (Angew. Chem., Int. Ed., 2013)

(untitled) - Zhou, J.-Q.; Sheng, W.-J.; Jia, J.-H.; Ye, Q.; Gao, J.-R.; Jia, Y.-X. (Tetrahedron Lett., 2013)

(untitled) - Yang, G.; Shen, C.; Zhang, W. (Angew. Chem., Int. Ed., 2012)

(untitled) - Chen, M.-W.; Chen, Q.-A.; Duan, Y.; Ye, Z.-S.; Zhou, Y.-G. (Chem. Commun., 2012)

(untitled) - Fujioka, M.; Morimoto, T.; Tsumagari, T.; Tanimoto, H.; Nishiyama, Y.; Kakiuchi, K. (J. Org. Chem., 2012)

(untitled) - Yu, X.; Wang, Y.; Wu, G.; Song, H.; Zhou, Z.; Tang, C. (Eur. J. Org. Chem., 2011)

(untitled) - Guo, S.; Xie, Y.; Hu, X.; Xia, C.; Huang, H. (Angew. Chem., Int. Ed., 2010)

(untitled) - Wang, Z.-Q.; Feng, C.-G.; Xu, M.-H.; Lin, G.-Q. (J. Am. Chem. Soc., 2007)

(untitled) - More, V.; Rohlmann, R.; García Mancheño, O.; Petronzi, C.; Palombi, L.; De Rosa, A.; Di Mola, A.; Massa, A. (RSC Adv., 2012)

(untitled) - Tiso, S.; Palombi, L.; Vignes, C.; Di Mola, A.; Massa, A. (RSC Adv., 2013)

(untitled) - Tiso, S.; Massa, A. (J. Heterocycl. Chem., 2015)

(untitled) - Vetica, F.; de Figueiredo, R. M.; Orsini, M.; Tofani, D.; Gasperi, T. (Synthesis, 2015)

(untitled) - Wang, Y.; Lu, H.; Xu, P.-F. (Acc. Chem. Res., 2015)

(untitled) - Chauhan, P.; Mahajan, S.; Kaya, U.; Hack, D.; Enders, D. (Adv. Synth. Catal., 2015)

(untitled) - Novacek, J.; Waser, M. (Eur. J. Org. Chem., 2014)

(untitled) - Perillo, M.; Di Mola, A.; Filosa, R.; Palombi, L.; Massa, A. (RSC Adv., 2014)

(untitled) - Tiffner, M.; Novacek, J.; Busillo, A.; Gratzer, K.; Massa, A.; Waser, M. (RSC Adv., 2015)

(untitled) - Johnson, K. M.; Rattley, M. S.; Sladojevich, F.; Barber, D. M.; Nuñez, M. G.; Goldys, A. M.; Dixon, D. J. (Org. Lett., 2012)

(untitled) - Massa, A.; Rizzo, P.; Monaco, G.; Zanasi, R. (Tetrahedron Lett., 2013)

(untitled) - Inokuma, Y.; Kwon, J. H.; Ahn, T. K.; Yoo, M.-C.; Kim, D.; Osuka, A. (Angew. Chem., Int. Ed., 2006)

(untitled) - Edwards, L.; Gouterman, M.; Rose, C. B. (J. Am. Chem. Soc., 1976)

WO Patent Appl. - Akerman, M.; Cardozo, M.; Houze, J. B.; Li, A. R.; Liu, J.; Liu, J.; Ma, Z.; Medina, J. C.; Schmitt, M. J.; Sharma, R.; Sun, Y.; Wang, Y.; et al. (Bicyclic carboxylic acid derivatives useful for treating metabolic disorders, 2007)

(untitled) - Rao, I. N.; Prabhakaran, E. N.; Das, S. K.; Iqbal, J. (J. Org. Chem., 2003)

(untitled) - Petronzi, C.; Collarile, S.; Croce, G.; Filosa, R.; De Caprariis, P.; Peduto, A.; Palombi, L.; Intintoli, V.; Di Mola, A.; Massa, A. (Eur. J. Org. Chem., 2012)

(untitled) - Krapcho, A. P.; Weimaster, J. F.; Eldridge, J. M.; Jahngen, E. G. E., Jr; Lovey, A. J.; Stephens, W. P. (J. Org. Chem., 1978)

(untitled) - Lafrance, D.; Bowles, P.; Leeman, K.; Rafka, R. (Org. Lett., 2011)

(untitled) - Allin, S. M.; Northfield, C. J.; Page, M. J.; Slawin, A. Z. M. (J. Chem. Soc., Perkin Trans. 1, 2000)

(untitled) - Klapars, A.; Huang, X.; Buchwald, S. L. (J. Am. Chem. Soc., 2002)